Petrologia e evolução crustal das rochas de alto grau de Porto Nacional - TO - GORAYEB, Paulo Sérgio de Sousa (Universidade Federal do Pará, 2017)
The Porto Nacional region, located at central-southern portion of the Tocantins State, is part of Structural Tocantins Province. That region forms a crustal segment mainly composed by granulitic and gneissic terraines, with a wide variety of lithotypes due to the effects of successive magmatic, sedimentary, tectonic and metamorphic processes during the Precambrian Eon. In the oldest units, from the Lower Proterozoic, have been recognized orthoderived rocks, as tholeiitic basalts type TH-1, calc-alkaline basalts and tonalites as well as paraderived rocks as graywackes, pelites, graphitic and silicic-iron-manganesiferous, submited to high grade metamorphism (Porto Nacional Complex, Morro do Aquiles Formation). Another set of rocks includes tonalites associated with minor granodiorites and granites, occurring along with a supracrustal sequence made up of calc-silicate gnaisses, pelites, psamites and gondites, metamorphosed in the amphibolite facies (Rio dos Mangues Complex). Meta-igneous bodies of anorthositic (Carreira Comprida Anorthosite), nepheline-sienitic (Estrela Suite) and K-rich granitic rock compositions (Matança and Serrote Suite), metamorphosed in the amphibolite facies, constitutes batholites and stocks enclosed by the former units. They represent magmatic events of different origins and ages. Other units from the end of Lower Proterozoic are represented by the Monte do Carmo Formation, composed by conglomerates, arkoses, graywackes and acid to intermediary volcanic rocks, and the Lajeado Suite, which encloses a set of granites. These unites represent intra-continental volcanic and plutonic magmatic processes related to extensional tectonic environment. The Upper Proterozoic and the Phanerozoic are represented, respectivelly, by psamo-pelites low grade metassediments (Natividade Group) and by sedimentary rocks of the Parnaiba Basin (Serra Grande and Pimenteiras Formations). The tectono-structural framework is here designed by the Tocantins Shear Belt, which trends NE-SW between the Amazônico and Paramiririm Archean cratons. This belt defines a regional imbricated system wide about 300 km, where mixed segments of different crustal level. The evolution of the belt is related to the oblique colision of Porangatu and Araguacema crustal blocks during the Lower Proterozoic, and to late transcurrent shears. The metamorphic studies developed in the Tocantins Shear Belt allowed characterize rocks of high grade metamorphism (Domine 1), with maximum temperature of 850°C and pressure of 8 kbar, which indicate that the rocks reached the granulite facies in a depth of about 30-35 km. The second terrain (Domine 2) includes rocks of high amphibolite facies with temperatures of 680°C and pressures of 6-5 kbar, indicating depths of about 20 km. The Domine 3 includes a migmatized gnaissic terrain, that underwent a middle to high amphibolite facies metamorphism, above the hornblende isograde and the curve of granite melt in high H2O activity. The petrogenetic records suggest a anticlockwise P-T-t path for the high grade metamorphism. This path is initially progressive with an increase of temperature, and crosses muscovite, biotite, andaluzite, garnet and sillimanite isogrades in the aluminous sequences, and hornblende, clivo and orthopyroxene in mafic compositions. The metamorphic path cross cuts the curve of granite melt in low H2O activity and generates S-type granites, and charnockites. The thermal peak is reached near 880°C and is followed by a significative increasing in pressure, with the stabilization of kyanite and garnet. Later, there was stablished retrograde pattern whose records suggest an overprinting in amphibolite and greenschist facies conditions at temperatures lower than 600°C and pressures about 5 kbar. The geochronologic data obtained by whole-rock Rb-Sr and single zircon Pb evaporation analysis suggests a minimum ages 2,1 - 2,2 Ga for the high grade metamorphism, indicating effects of the Transamazonian thermo-tectonic event. The petrogenetic interpretations based on lithochemical and tectonic data, suggest that the evolution of the high grade rocks may be related to the rupture of the pre-existent Archean crust. In this crust affected by extensional tectonism, and strongly controled by magmatic underplating, restricted oceans were installed. The crustal evolution was followed by A subduction, delamination and crustal-stacking wedge, which end up with the transportation of infracrustal segments to upper leveis of the crust.